Investigation of vehicle ride height and diffuser ramp angle on downforce and efficiency. (July 2019) - Knight, Jason; Spicak, Milan; Kuzenko, Antons; Haritos, George; Ren, Guogang
Diffusers are typically used in motorsport to generate negative lift (downforce). They also reduce aerodynamic drag and so significantly enhance aerodynamic efficiency. The amount of downforce generated is dependent on ride height, diffuser ramp angle and its relative length to that of the vehicle length. This paper details a numerical investigation of the effects of ride height and diffuser ramp angle in order to find an optimum downforce and efficiency for the inverted Ahmed model. A short and long diffuser with ratios of 10% and 35%, respectively, to that of vehicle length are studied. The short diffuser produced lower maximum downforce and efficiency at a lower ride height and lower angle when compared to the longer diffuser. The long diffuser produced highest downforce and the best efficiency with a ramp angle of 25° at ride height ratio of 3.8% when compared to vehicle length. Different ride heights were found to correspond to different diffuser ramp angles to achieve optimum downforce and efficiencies.